Initial Access through Beamforming in mmWave - Christina, G. (IRO Journal on Sustainable Wireless Systems, 2020)
Future Wi-Fi, 5G Cellular and millimetre-wave (mmWave) will depend on highly directional links in order to prevail over exuberant path loss experienced in the different bands of frequency. However, in order to establish these type of links, the receiver and transmitter need mutual discovery which will result in high energy consumption and large latency. The proposed work deals with reduction of energy consumption and latency significantly with the help of a fully digital front-end. The digital beamformer will receive the spatial samples within a shot, from all directions. However, in analog front-ends, sampling is allowed for beamforming in one particular direction at a time resulting in the time period in which the mobile is "on" for longer. This will result in an increase in energy consumption by more than four times for the analog front-end when compared with digital front-ends, taking into consideration the antenna arrays' size. However, from the power consumption point of view, using a fully digital beamforming post beam discovery is not recommended. Hence in order to overcome this drawback, a digital beamformer coupled with a 4-bit A-D convertor with low resolution is proposed. The use of low resolution will decrease the power consumption such that it is in the same zone as that of analog beam forming while it is possible to make use of the fully digital beamforming spatial multiplexing capabilities resulting in improved energy efficiency and reduced discovery latency.
Keywords: Digital beamformer; analog beam former; path loss; directional links